Multiple Culprit Coronary Artery Thrombosis in a Patient with Coronary Ectasia - Bruno da Silva Matte; Gustavo Neves de Araujo; Felipe Homem Valle; Ana Maria Rocha Krepsky (Case Reports in Cardiology)
We here report a case of ST-elevation myocardial infarction (STEMI) due to simultaneous acute coronary artery occlusions of two major coronary arteries in a patient with coronary ectasia. The patient had been previously submitted to percutaneous coronary angioplasty with bare metal stent implantation in both culprit vessels. Very late stent thrombosis could be the cause of the first occlusion, triggering the event in the other vessel. In addition, concomitant embolic sources were not identified. Although routine aspiration thrombectomy in STEMI was not proven to be beneficial in randomized clinical trials, it was of great value in this case. We also discuss the relation between coronary ectasia, chronic inflammatory status, and increased platelet activity which may have caused plaque disruption in another already vulnerable vessel.